2022
DOI: 10.1136/bmjopen-2021-058369
|View full text |Cite
|
Sign up to set email alerts
|

Risk of SARS-CoV-2 infection among front-line healthcare workers in Northeast Brazil: a respondent-driven sampling approach

Abstract: ObjectivesWe assessed the prevalence of SARS-CoV-2 infection, personal protective equipment (PPE) shortages and occurrence of biological accidents among front-line healthcare workers (HCW).Design, setting and participantsUsing respondent-driven sampling, the study recruited distinct categories of HCW attending suspected or confirmed patients with COVID-19 from May 2020 to February 2021, in the Recife metropolitan area, Northeast Brazil.Outcome measuresThe criterion to assess SARS-CoV-2 infection among HCW was … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 34 publications
0
10
1
Order By: Relevance
“…We found in the literature that COVID-19 could be spread through aerosol/ aerated solids, fluid from human secretions, droplets from normal breathing, coughing, sneezing and surface contact, and, thus, it is considered to be very contagious [ 3 ], and that nurses are extremely exposed to COVID-19 since they have a direct contact with COVID-19 patients, especially in the context of AGPs [ 9 , 12 , 31 ]. In managing the health workers exposure risk, and to avoid any contamination with COVID-19 during aerosols, the use of PPE is recommended for eye, face and head protection, together with reusable equipment (glasses, visors or face shields) [ 17 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found in the literature that COVID-19 could be spread through aerosol/ aerated solids, fluid from human secretions, droplets from normal breathing, coughing, sneezing and surface contact, and, thus, it is considered to be very contagious [ 3 ], and that nurses are extremely exposed to COVID-19 since they have a direct contact with COVID-19 patients, especially in the context of AGPs [ 9 , 12 , 31 ]. In managing the health workers exposure risk, and to avoid any contamination with COVID-19 during aerosols, the use of PPE is recommended for eye, face and head protection, together with reusable equipment (glasses, visors or face shields) [ 17 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The case of South America was analysed in one study. The rates of SARS-CoV-2 infection among HCW in São Paulo city ranged from 5.5% (IgG ELISA) in a private hospital to 14% (IgG/IgM antibody, WONDFO) in a large public hospital in 2020 due to adoption of high-quality hospital infection control and provision of complete PPE in the early stages of the COVID-19 pandemic [ 31 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In Brazil, a study on 1,525 health workers reported a distribution of 525 medical doctors, 471 registered nurses, 263 nursing assistants, and 264 physiotherapists (19) . Although the authors found that women predominated in all categories (81.1%; 95% CI: 77.8% to 84.1%), their percentages are much higher than the ones observed in this study (63.6%; 95% CI: 59.9-67.3).…”
Section: Discussionmentioning
confidence: 99%
“…The coronavirus disease 2019 (COVID- 19) was originally identified in the city of Wuhan, China, in December 2019. Current evidence indicates that the COVID-19-causing virus is transmitted person-toperson through direct contact and droplets.…”
Section: Introductionmentioning
confidence: 99%
“…Given the unprecedented nature of COVID-19, there are very few studies describing the challenges of conducting RDS during the pandemic. Yet evidence suggests that RDS was effectively used during COVID-19 to recruit men that have sex with men in Portugual (MSM) ( 13 ); isolated positive COVID-19 cases in Finland ( 14 ); and frontline care workers in Vietnam ( 15 ), Canada ( 16 ) and Brazil ( 17 ). Although Stark et al employed RDS to recruit a sample of people who inject drugs (PWID) in the rural United States during the pandemic to document the impact on substance use behaviors and overdose risk perception ( 18 ), to our knowledge, no study of PWID or HIV populations has been conducted employing RDS methods.…”
Section: Introductionmentioning
confidence: 99%